A new species of snail-eating snakes of the genus Pareas Wagler, 1830 (Reptilia: Serpentes) from eastern Himalayas, India - Bhosale, Harshal; Phansalkar, Pushkar; Sawant, Mandar; Gowande, Gaurang; Patel, Harshil; Mirza, Zeeshan A. (European Journal of Taxonomy, 2020)
A new species of snail-eating snakes of the genus Pareas Wagler, 1830 is described from the eastern Himalayas. The species Pareas kaduri sp. nov. differs from all known species of the genus in bearing the following suite of characters: SVL 455–550 mm, TaL/TL 0.184–0.207, brown dorsum with black transverse bands throughout the body, 15 dorsal scale rows throughout the body and mid-dorsal vertebral scale rows enlarged, 8 rows keeled in males, loreal not touching orbit, ventrals 160–183, subcaudals 65–70 in males, 52 in one female specimen, hemipenis short, unilobed and 6–7 maxillary teeth. Molecular data for mitochondrial 16S rRNA and cytochrome b genes further attest the distinctness of the new species, which was recovered as a member of the Pareas hamptoni clade. Our work brings the total number of species recognized within the genus Pareas to 20.